Advanced techniques for cooperation and physical layer security in visible light communications - Su, Nuğman. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Visible light communications (VLC), enabling high-rate data transfer over the idle visible light spectrum, can contribute to alleviating the congestion problem ac cumulating in the radio-frequency spectrum. This thesis deals with two important aspects of VLC: i) efficient cooperation techniques adapted to the intensity-modulated light-emitting-diode (LED) transmitters, ii) secure multi-user communication schemes based on the multiple-input-multiple-output (MIMO) framework. Firstly, 3-terminal full-duplex (FD) cooperative VLC systems are considered where both transmitters (source and relay) are subject to the LED clipping distortion effects. Transmission rate maximizing optimum power allocation (OPA) strategies are proposed for both the amplify-and-forward (AF) and decode-and- forward (DF) relaying capabilities. Next, the physical layer security (PLS) problem is considered for the multi-user MIMO- VLC systems with an eavesdropper (Eve). To ensure PLS, two transmit precoding schemes are proposed, based on generalized space shift keying and receive spatial modulation, respectively. The received signals of the legitimate users are optimized jointly, such that their bit error rates (BERs) are minimized and Eve’s BER is significantly degraded. To be able to support massive amount users and further degrade Eve’s reception, non orthogonal multiple access (NOMA) and random constellation coding techniques are also utilized. For both cases, the achievable secrecy rates and bounds are derived an alytically. The BER and secrecy performance results obtained by simulations confirm that the proposed frameworks ensure PLS for legitimate users.
Keywords: Optical communications.